Nonlinear dynamics of guyed masts under wind load: Sensitivity to structural parameters and load models. Issue 169 (October 2017) - Ballaben, Jorge S.; Guzmán, Alberto M.; Rosales, Marta B.
Abstract: As the wireless communications spread, there is an increasing demand of antenna supporting structures. Guyed lattice towers (masts) are chosen for economical reasons when there is enough space for their location. Radio and television industries employ structures that can attain heights up to 600 m and communication towers for mobile phones are approximately 60 m though higher structures are also constructed. For the latter, guyed masts are indicated. Nowadays, the demand for more accurate and reliable communication systems poses more stringent structural requirements since to attain high quality in signal transmission, small magnitude motions of the supporting structures are usually needed. The design of these structures is, in general, carried out following the standard codes and simplified models. Despite the large potential of adverse impact, the dynamic actions as wind and earthquakes, are not usually addressed in detail with exception of special cases. In this work, a parametric study on the effect of three relevant parameters (i.e. guy pretension, structural damping, mast stiffness) on a guyed mast is carried out. A typical structure under wind load is analyzed using a finite element model. Two load representations are employed; the mean component is obtained following procedures from standards and is the same for both load models. The fluctuating part of the wind load is then added. In the first model, the turbulent component is represented by a time series obtained by means of the Spectral Representation Method including temporal and spatial correlations. The second model is a simpler approach, in which the temporal component of the wind load is represented through a harmonic function. The resulting transverse displacements and cable tensions histories are analyzed to assess the dynamic structural response. It is observed that the structure is more sensitive to the guy pretension when compared with the other two variable parameters. Also, it was verified that the stochastic load is a more adequate option to model the wind. These two findings are crucial in the design of this type of structures. Highlights: A parametric sensitivity study of a guyed mast dynamic response is carried out. Two dynamic wind load models are used (stochastic and harmonic). The chosen parameters are: guy tension, structural damping and mast stiffness. The structure shows a higher sensitivity to the guy tension variation. The stochastic load is more adequate to model the wind action.